2011
DOI: 10.1603/me10230
|View full text |Cite
|
Sign up to set email alerts
|

Aedes albopictus (Diptera: Culicidae) Population Size Survey in the 2007 Chikungunya Outbreak Area in Italy. I. Characterization of Breeding Sites and Evaluation of Sampling Methodologies

Abstract: The population of Aedes albopictus (Skuse) (Diptera: Culicidae) was measured in four towns in northern Italy by means of Stegomyia indices (house index: percentage of houses with at least one active breeding site; container index: percentage of containers with larvae; and Breteau index: number of active breeding sites per premises), pupae per premises index (PPI), pupae per hectare index (PHI), and ovitrap monitoring. A detailed investigation on types and number of productive or potential larval habitats in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 30 publications
3
46
1
1
Order By: Relevance
“…Aedes albopictus (Skuse) is an invasive species rapidly spreading and establishing in a number of countries with different climates (Benedict et al 2007) and it is known to be an efÞcient vector of many arboviruses causing human diseases, including yellow fever (family Flaviridae, genus Flavivirus, YFV), dengue (family Flaviviridae, genus Flavivirus, DENV), and Chikungunya (family Togaviridae, genus Alphavirus, CHIKV), in tropical as well as in temperate regions (Carrieri et al 2011a). Moreover, Ae.…”
mentioning
confidence: 99%
“…Aedes albopictus (Skuse) is an invasive species rapidly spreading and establishing in a number of countries with different climates (Benedict et al 2007) and it is known to be an efÞcient vector of many arboviruses causing human diseases, including yellow fever (family Flaviridae, genus Flavivirus, YFV), dengue (family Flaviviridae, genus Flavivirus, DENV), and Chikungunya (family Togaviridae, genus Alphavirus, CHIKV), in tropical as well as in temperate regions (Carrieri et al 2011a). Moreover, Ae.…”
mentioning
confidence: 99%
“…This can be explained by the presence of numerous man-made containers, which are the main sources of Ae. albopictus populations in urban or peri-urban environments [51]. Urbanization has been related to an increase in the larval habitats, mosquito density, larval development rate, and adult survivorship of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods, such as ovitrap collections or a pupal survey, have been recommended to estimate IMS abundance [27,28]. In the Emilia-Romagna region of Italy, Carrieri et al [51,60] demonstrated a positive correlation between the number of Ae. albopictus eggs collected in ovitraps, female density estimated by a pupal survey, and human landing collections (HLC); and in Rome, Italy, Manica et al [61] estimated an increase of one biting female per person collected by HLC for every five additional eggs observed in ovitraps.…”
Section: Discussionmentioning
confidence: 99%
“…Ae. albopictus, the other vector, is already established in various countries in Europe, such as Italy, the south of France and some regions in Spain [26,[27][28][29]. In Spain, the mosquito is found in most parts of Catalonia, the region where most of our cases (9/10) were residing, and in the Baleares islands as well as some territories of Murcia and Valencia [26].…”
Section: Discussionmentioning
confidence: 99%